Export Instability and Policy Implications for Developing Countries. (IMF Working Papers; Working Paper ;, 1990)
A study by the author published in 1988 proposed the hypothesis that export instability depends upon the level of industrialization of the exporting country and the position of exports in the product cycle (growth or mature products). This paper provides further empirical evidence in support of the hypothesis. The paper discusses the significance of the empirical findings, explains why diversification has increased export instability in many developing countries, and discusses the policy implications of the findings. The paper also analyzes the effects of data aggregation on empirical results and suggests topics for future research.